EKSISTENSI PEMIKIRAN JOHN DEWEY DALAM PENDIDIKAN DI INDONESIA - Privera Ajeng Ersanda (LP4MK STKIP PGRI Lubuklinggau, 2022)
The article discusses the existence of John Dewey's thoughts in education in Indonesia. The background of this research is the researcher's interest in the contribution of John Dewey's thoughts to education in Indonesia. From this, the researcher will conduct an assessment of the life history of John Dewey, the nature of education based on the views of John Dewey and the contribution of John Dewey in the world of education in Indonesia. Then the method used in writing this article is the historical method which consists of four stages. The first stage is heuristics, while the second stage is criticism of historical sources (verification), then the third stage is analysis of historical facts (interpretation) and the last or fourth stage is the presentation in writing history (historiography). Based on the research obtained from the literature review, it was found that the views or thoughts of John Dewey cannot be separated from the nature of education. Because John Dewey is a figure who pioneered the philosophy of education, namely progressivism. John Dewey's view of progressivism gives a considerable influence and contribution to the development of the 2013 Curriculum in Indonesia. This is because progressivism thinking prioritizes children as students' subjects to develop character education in their way of thinking, so as to improve the quality of skills, knowledge and attitudes of students.